DIFFERENT MAIZE SILAGE CULTIVARS WITH OR WITHOUT UREA AS A FEED FOR RUMINANT: CHEMICAL COMPOSITION AND IN VITRO FER-MENTATION AND NUTRIENT DEGRADABILITY - Sallam, Sobhy M.A; Rady, Asmaa M. S.; Attia, Marwa F. A.; Elazab, Mahmoud A.; Vargas-Bello-Pérez, Einar; Kholif, Ahmed E. (Chilean Journal of Agricultural & Animal Sciences, 2024)
This study compared forage yield and agronomic characteristics of 9 maize cultivars (Pioneer 30N11, Pioneer 4444, Pioneer 30K08, SC-128W, SC-166Y, SC-78Y, TWC-324W, TWC-368Y and TWC-321W) ensiled with or without urea as for ruminants on in vitro ruminal fermentation characteristics and nutrient degradability. A factorial randomized complete block design was used. Pioneer 30N11 and Pioneer 4444 showed the greatest silage forage yield, ear weight, and plant height. The chemical composition of maize silage cultivars without urea revealed that Pioneer 30K08 had the greatest (P<0.001) crude protein (CP) content (127 g/kg), while the lowest CP content (89 g/kg) was observed with SC-78Y. CP content ranged from 118 to 156 g/kg when urea was added to the maize silage cultivars. The neutral detergent fiber, acid detergent fiber, and acid detergent lignin contents recorded the highest values (P<0.01) in TWC-324W, SC-128W and SC-78Y. Urea treatment of different cultivars affected (P?0.05) the concentrations of CP, ether extract (EE), non-structural carbohydrates (NSC), and fibers. Urea treatment increased CP and EE in all cultivars and increased or decreased truly degraded dry matter (TDDM), truly degraded organic matter (TDOM), protozoa, ammonia and methane (P?0.05). Overall, Pioneer 30N11, Pioneer 4444 and Pioneer 30K08 showed the greatest forage yield and nutritive value as a feed for ruminants.